Critical Analysis of Comprehensive Care Approaches for Diverse Patient Needs - SHAKWAN, MAHDI ALI; AL YAMI, NIZAR SALEH ABDULLAH; AL HIDER, FARIS ALI MANA; ALQAHS, YASSER AHMED ABDULLAH; ALSHAHI, HOSSAIN MOHAMMAD HOSSAIN; AL ALSHAHI, HUSSAIN ABDULLAH; AL SHAHI, TURKI MANE ALI; AL SALAMAH, ABDULRHMAN SALEM; HAMAD, HAMAD ABDULLAH; ALYAMI, MOMHAMMAD AHMED SAUD (Journal of Ecohumanism, 2024)
Coordinated care, we talk about the healthcare model, which focuses on a patient’s physical, psychological, social, and cultural aspects. Especially with the diversification of patients, the strategy of touching individual approach has become vital. This paper explains the extent to which comprehensive care models address diverse patient needs while evaluating how the models meet patient health needs, decrease disparities, and increase satisfaction. The main findings of the research are based on the examples of various healthcare contexts, and the advantages of presenting integrated care teams, focusing on social determinants, and providing culture-sensitive care are discussed. However, barriers to the expansion of CC continue to surface, which concerns mainstream parts of practical consideration such as funding, staff development deficiencies, and some practitioners. This paper has discussed various barriers to equity in healthcare delivery to different patient groups; this paper concludes with measures drawn toward eliminating such barriers.